(3aUd aj GdeSM Ydi GdNajfs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3aUd ai CbhGd GdYdeGA ai GdeSM Ydi GdNajf gd ef TQWg Cf jchf GdNa Zj eNQb MJi dG jXgQ TF ef GdbOe s
(3BNQgG (B:s
(3abO MUd GdebUhO ef EJdGagG dcf gh EKe HJdhjK GdeSLO ajDeQ HJWgjQg HNdGa GdESJLeGQ HJeGe GdKdGK aEf ajg aYd JeGe GdeCehQ hJMUjd GdebUhO JeJ GdQSGdI GdeHGQcI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs